Doing digital methods - Rogers, Richard (Sage Publications, 2023)
"Teaching the concrete methods needed to use digital devices, search engines and social media platforms to study some of the most urgent social issues of our time, this is the essential guide to the state of the art in researching the natively digital. With explanation of context and techniques and a rich set of case studies, Richard Rogers teaches you how to: Build a URL list to discover internet censorship Transform Google into a research machine to detect source bias Make Twitter API outputs comprehensible and tell stories Research Instagram to locate 'hashtag publics' Extract and fruitfully analyze Facebook posts, images and video And much, much more"--